ALGORITHMS OF MULTI FREQUENCY RADIOMETRY IN THE CONDITIONS OF BROADBAND INTERFERENCE - Orlov, V. V.; Lytvynenko, O. A.; Galanin, V. V. (Одеські астрономічні публікації, 2018)
The development of digital technologies for multi-frequency signal reception in the low-frequency range creates the prerequisites for the application of optimal algorithms for real-time beamforming without changing the aperture of the radio telescope antenna. In the present paper, a model of the system based on multiplicative processing (MP) is considered and investigated. The system consists of two antenna arrays, the signals from the outputs of which pass through the narrow-band filters of receiving devices. After filtration, they undergo MP and weighted summation. Next, we consider an algorithm for the formation of a narrow beam of the antenna pattern (AP) of a multi-frequency radio interferometer based on the well-known cosinusoid summation method. Its meaning lies in summing up the results of multiplicative processing of signals from the outputs of several spatially separated different scales bases. In work, using MP, a method is proposed for reducing the width of the main lobe of AP on one base by receiving signals at several frequencies. The further development of the method is associated with the optimization of the AP in multi-frequency MP, which leads to the possibility of lowering the side-lobe levels by weighing the signals from the outputs of the MP channels. For this purpose, for the sum of odd cosine waves, it is necessary to determine the weighting factors that ensure the minimum root-mean-square level of side lobes in a given zone of AP suppression. As a result of MP processing, we obtain a decrease in the amplitudes of side lobes with an insignificant increase in the width of the antenna pattern of the antenna system. In work the algorithm of suppression of broadband hindrances is also considered. The synthesis of the optimization algorithm is reduced to the need to determine the weighting coefficients and frequencies that provide the minimum rms level of the side lobes of the AP in a given zone of suppression, with a limited range of frequency separation. These methods are proposed to use in radio astronomy to improve the quality of research.